Mechanism study on a plague outbreak driven by the construction of a large reservoir in southwest china (surveillance from 2000-2015). - Xin Wang; Xiaoyu Wei; Zhizhong Song; Mingliu Wang; Jinxiao Xi; Junrong Liang; Yun Liang; Ran Duan; Kecheng Tian; Yong Zhao; Guangpeng Tang; Lv You; et al. (Public Library of Science (PLoS), 2017)
BACKGROUND:Plague, a Yersinia pestis infection, is a fatal disease with tremendous transmission capacity. However, the mechanism of how the pathogen stays in a reservoir, circulates and then re-emerges is an enigma. METHODOLOGY/PRINCIPAL FINDINGS:We studied a plague outbreak caused by the construction of a large reservoir in southwest China followed 16-years' surveillance. CONCLUSIONS/SIGNIFICANCE:The results show the prevalence of plague within the natural plague focus is closely related to the stability of local ecology. Before and during the decade of construction the reservoir on the Nanpan River, no confirmed plague has ever emerged. With the impoundment of reservoir and destruction of drowned farmland and vegetation, the infected rodent population previously dispersed was concentrated together in a flood-free area and turned a rest focus alive. Human plague broke out after the enzootic plague via the flea bite. With the construction completed and ecology gradually of human residential environment, animal population and type of vegetation settling down to a new balance, the natural plague foci returned to a rest period. With the rodent density decreased as some of them died, the flea density increased as the rodents lived near or in local farm houses where had more domestic animals, and human has a more concentrated population. In contrast, in the Himalayan marmot foci of the Qinghai-Tibet Plateau in the Qilian Mountains. There are few human inhabitants and the local ecology is relatively stable; plague is prevalence, showing no rest period. Thus the plague can be significantly affected by ecological shifts.